(untitled) (Editora Impacto Científico, 2025)
Chagas disease (CD) is more prevalent in tropical and humid regions. The disease remains a public health problem in several regions of the world, particularly in endemic areas, as observed in several South American countries. Drug treatment in the acute phase of the disease is effective but has limitations related to tolerance, which worsens in immunosuppressed patients. Therefore, this study aimed to evaluate the relationship between benznidazole intervention in immunosuppressed patients and survival prognosis. To achieve this objective, a secondary study was conducted through a systematic literature review. The Medline/pubmed and Scielo databases were searched without date or language restrictions. The variables evaluated included the clinical presentation for different types of immunosuppression, the pattern of CD reactivation in immunosuppressed patients, and its relationship with the use of other forms of intervention such as ketoconazole, benznidazole, and nifurtimox. Few studies were eligible for retraction regarding the relationship between CD and immunosuppression and pharmacological intervention with benznidazole, but four case reports and two reviews were available. The data evaluated demonstrate that intervention can vary depending on the symptomatology and/or clinical presentation of the patients. Regarding the efficacy of benznidazole, indicated as primary prophylaxis, of the four clinical cases reported, two (50%) resulted in death. Other factors were certainly linked to patient outcomes, such as age, timing of early or late diagnosis, severity of the clinical presentation, and use of primary and secondary prophylaxis. However, this approach generated a consistent indicator of the need for new approaches that interpret the diverse symptoms and clinical manifestations of CD in immunosuppressed patients and may lead to the emergence of new, more assertive protocols for disease intervention.